Odpowiedzi

Najlepsza Odpowiedź!
2009-12-09T02:00:48+01:00
A)
2x - y = 5
x + y = 4

3x = 9 |:3
x = 3

x = 3
3 + y = 4

x = 3
y = 4 - 3

x = 3
y = 1

b)
-x - y = -6
-x + y = 2

- 2x = - 4 |:(- 2)
x = 2

x = 2
- 2 + y = 2

x = 2
y = 2 + 2

x = 2
y = 4

c)
4x - 5y = -4
-2x + 3y = 1,1 |* 2

4x - 5y = - 4
-4x + 6y = 2,2

y = - 1,8

-4x + 6y = 2,2
y = - 1,8

- 4x - 10,8 = 2,2
y = - 1,8

-4x = 2,2 +10,8
y = - 1,8

-4x = 13 |:(-4)
x = -3,25

x = -3,25
y = - 1,8


d)
-2x + y = 0 |*3
3x - 3y = 1

-6x + 3y = 0
3x - 3y = 1

- 3x = 1 |:(-3)
x = -⅓

x = -⅓
3(-⅓) - 3y = 1

x = -⅓
- 1 - 3y = 1

x = -⅓
-3y = 2 |:(-3)

x = -⅓
y = -⅔

e)
|*(-2)
2x - 5y = -19 |* 3

-6x + 4y = 24
6x - 15y = - 57

-11y = - 33 |:(-11)
y = 3

3x - 2*3 = -12
y = 3

3x - 6 = -12
y = 3

3x = -12 + 6
y = 3

3x = -6 |: 3
y = 3

x = - 2
y = 3


5 3 5
2009-12-09T02:13:18+01:00
A)
2x - y = 5
x + y = 4
---------
3x=9 /:3
x=3

y=4-x
y=4-3=1

x=3
y=1

b)
-x - y = -6
-x + y = 2
--------------
-2x=-4 /:(-2)
x=2

y=2+x
y=2+2=4

x=2
y=4

c)
4x - 5y = -4
-2x + 3y = 1,1 /*2

4x-5y=-4
-4x+6y=2,2
-------------
y=2,2-4
y=-1,8

4x=-4+5y
4x=-4+5*(-1,8)
4x=-4-9
4x=-13 /:4
x=-3 ¼

x=-3 ¼
y=-1,8

d)
-2x + y = 0 /*3
3x - 3y = 1

-6x+3y=0
3x-3y=1
----------------
-3x=1 /:(-3)
x=-⅓

y=2x
y=2*(-⅓)=-2/3

x=-⅓
y=-2/3

e)
3x - 2y = -12 /*(-2)
2x - 5y = -19 /*3

-6x+4y=24
6x-15y=-57
---------------------
-11y=-33 /:(-11)
y=3

2x=-19+5y
2x=-19+5*3=-19+15
2x=-4 /:2
x=-2

x=-2
y=3
2009-12-09T07:44:01+01:00
A
2x - y = 5
x + y = 4

3x=9/:3
x=3

2*3-y=5
6-y=5
-y=5-6
-y=-1/:(-1)
y=1
odp. x=3, y=1

b
-x - y = -6
-x + y = 2
-2x=-4/:(-2)
x=2
-2-y=-6
-y=-6+2
-y=-4/:(-1)
y=4
odp. x=2, y=4

c
4x - 5y = -4
-2x + 3y = 1,1/*2
4x-5y=-4
-4x+6y=2,2
y=-1,8
4x-5*(-1,8)=-4
4x+9=-4
4x=-4-9
4x=-13/:4
x= -13/4=-3,25
odp. x=-3,25 y=-1,8

d
-2x + y = 0/*3
3x - 3y = 1
-6x+3y=0
3x-3y=1
-3x=1/:(-3)
x= -1/3
-2*(-1/3)+y=0
2/3+y=0
y=-2/3
odp. x=-1/3, y=-2/3

e
3x - 2y = -12/*2
2x - 5y = -19/*(-3)
6x-4y=-24
-6x+15y=57
11y=33/:11
y=3
3x-2*3=-12
3x-6=-12
3x=-12+6
3x=-6/:3
x=-2
odp. x=-2, y=3